(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
The possibilities of using 2-Photon-Polymerisation (2PP) are presented, which is the technology behind Nanoscribe’s 3D microprinting, and highlight customer applications in the fields of of medicine and biology. This technology allows for the straightforward printing of virtually any 3D object, with linewidths and line-distances down to 0.2 µm and 0.5 µm, respectively. At the same time, it allows for total sample sizes in the range of several millimeters. The print results in a polymer object. Several biocompatible resins are available. Alternatively, methods are available to transfer the resulting geometry into other materials. With this technology, highly integrated microscopic parts can be created. Recent examples from the fields of medicine and biology will be presented, including: tools to interact with individual cells, tissue models, 3D components for lab-on-a-chip applications, and microscopic tools for surgery.